The Antioxidant and Enzyme Inhibitory Potential of n-Hexane-Extracted Oils Obtained from Three Egyptian Cultivars of the Golden Dewdrop Duranta erecta Linn. Supported by Their GC-MS Metabolome Analysis and Docking Studies - Shaimaa Fayez; Gokhan Zengin; Sara T. Al-Rashood; Mahmoud A. El Hassab; Wagdy M. Eldehna; Stefano Dall'Acqua; Omayma A. Eldahshan (MDPI AG, 2022)
Duranta erecta Linn. has a longstanding history for use in folk remedy for several disorders. Its hydroalcoholic extract has been investigated intensely in the treatment of many ailments, but to date very few data are presented to explain the pharmacological use of its oil. In this study, the chemical profiles of the leaf oils extracted from three Egyptian Duranta erecta cultivars, namely 'Green', 'Golden edge', and 'Variegata' are traced using GC-MS analysis. D. erecta 'Green' showed predominance of vitamin E (22.7%) and thunbergol (15%) whereas D. erecta 'Golden edge' and 'Variegata' contained tetratetracontane as a major component in their oils. The highest phenolic and flavonoid contents, displayed as gallic acid and rutin equivalents per gram oil, respectively, were observed in the 'Golden edge' and 'Variegata' cultivars, which was reflected by their strong DPPH and ABTS scavenging activities as well as the highest reducing power in both CUPRAC and FRAP assays. D. erecta 'Green' displayed better metal chelating potential, which may be attributed to its content of vitamin E. All cultivars showed similar enzyme inhibitory profiles. The best inhibition of α-glucosidase and α-amylase was observed by D. erecta 'Green'. In silico studies of the major constituents docked on the active sites of the target enzymes NADPH oxidase, amylase, glucosidase, butyrylcholinesterase, and tyrosinase revealed high binding scores, which justified the biological activities of the tested oils.